Relationship of decreased amniotic fluid and perinatal outcome: a comparative study - Verma, Menka; Gupta, Surbhi; Ahuja, Meenu Vashist; Pratap, Charu (International Journal of Research in Medical Sciences, 2016)
Background: A decreased amniotic fluid volume is frequently one of the first clues to an underlying fetal abnormality or maternal diseased state. Isolated oligohydramnios may occur in late pregnancy in patients with no other high risk factors and diagnosed on routine ultrasound. This study was conducted to assess the effect of oligohydramnios on perinatal outcome at or beyond 34 weeks of gestation with amniotic fluid index (AFI) ≤ 5. Methods: 50 cases and equal controls were taken in the study which fulfilled the inclusion criteria. A written and informed consent was taken from all the subjects entering into the study. An ultrasound examination was performed on all the subjects entering the study. Phelan method was used for measurement of AFI. Measurement of the deepest pool in each quadrant was summated and AFI was recorded in centimeters. Results: Anthropometric variables were comparable in both the groups. The distribution of non-stress test (NST) and onset of labor was significantly different in both the groups. The presence of meconium stained liquor was non significantly same in both groups. Regarding neonatal outcome, birth weight less than 2.5 kg and APGAR score less than 7 was significantly higher in cases as compared to controls. Conclusions: Oligohydramnios (AFI< 5) was associated with more number of preterm deliveries, non-reactive NST, fetal distress and more NICU admissions. More studies are needed for defining threshold levels for measuring AFI.